Using Cooperative Learning in Formal and Nonformal Education - Katy J. Groseta; Brian E. Myers (EDIS)
AEC-381, a 4-page illustrated fact sheet by Katy J. Groseta and Brian E. Myers, describes the advantages of a teaching strategy where learners work in small groups, touches on some of the concerns educators might have, and offers several guidelines. Includes references. Published by the UF Department of Agricultural Education and Communication, November 2006.